MHD Mixed Convective Heat and Mass Transfer through a Stratified Nanofluid Flow Over a Thermal Radiative Stretching Cylinder - Maripala, Srinivas; Naikoti, Kishan (International Journal of Mathematical Research, 2016)
The flow problem presented in this paper is to study the heat and mass transfer characteristics of a mixed convection nanofluid flow along a stretching cylinder embedded in a thermally stratified medium are numerically analyzed, with the thermal radiation effects. The governing boundary layer equations of continuity, momentum, energy and concentration are transformed into a set of ordinary differential equations with the help of suitable local similarity transformations. The coupled non-linear ordinary differential equations are solved by the implicit finite difference method along with the Thomas algorithm. The effect of various material parameters such as buoyancy parameter, solutal buoyancy parameter, Prandtl number, radiation parameter, Schmidt number, curvature parameter, magnetic parameter, stratification parameter, Brownian motion parameter and thermophoresis parameter on the velocity, temperature and concentration profiles are presented in graphs. Physical quantities such as skin friction coefficient, Nusselet number and Sherwood number are also computed.